Identification of endomycorrhizal fungi colonizing roots by fluorescent single-strand conformation polymorphism-polymerase chain reaction. - Simon, L (1993)
A method to identify arbuscular endomycorrhizal fungi based on the amplification of portions of the nuclear gene coding for the small subunit rRNA is presented. By coupling the sensitivity of the polymerase chain reaction and the specificity afforded by taxon-specific primers, a variety of samples can be analyzed, including small amounts of colonized roots. Family-specific primers as well as generic primers are described and can be used to amplify small subunit rRNA fragments from endomycorrhizal fungi by polymerase chain reaction. The amplified products are then subjected to single-strand conformation polymorphism analysis to detect sequence differences. Among the advantages of this approach is the possibility of directly identifying the fungi inside field-collected roots, without having to rely on the fortuitous presence of spores. This technique should have obvious applications in the study of arbuscular endomycorrhizal fungi populations and allow closer examination of their host specificity.